1972
DOI: 10.1017/s0305004100050520
|View full text |Cite
|
Sign up to set email alerts
|

Some results in generalized homology, K-theory and bordism

Abstract: This paper is designed to pave the way for the author's work on the symplectic bordism ring MSp*(12), (13). We here discuss all the notation used, and collect together all the theorems quoted therein. At the same time, I hope that some of the results presented here might be of interest in their own right. Our central theme is the study of the hurewicz map e: S*(X) → E*(X), both in general and certain specific cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The only unknown in (2.6) is MSp*, since MSU*(MSp) is a free MSU*-module: it is this spectral sequence that we investigate thoroughly in [3]. Note that the corresponding spectral sequence for ko does not converge, since H*(KO; MSp*) is non-zero in negative dimensions.…”
Section: Algebraic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only unknown in (2.6) is MSp*, since MSU*(MSp) is a free MSU*-module: it is this spectral sequence that we investigate thoroughly in [3]. Note that the corresponding spectral sequence for ko does not converge, since H*(KO; MSp*) is non-zero in negative dimensions.…”
Section: Algebraic Methodsmentioning
confidence: 99%
“…The purpose of this note is to announce the author's computation of the symplectic bordism ring MSp* in dimensions < 20. The details will appear in two subsequent papers [3,4] and here we simply list the methods used and the results obtained.…”
Section: Introductionmentioning
confidence: 99%
“…By definition, this is the exponential series of F , and we wish to interpret it geometrically using a convenient variant of a method pioneered by Adams [1]. Given any spectrum F , the Boardman homomorphism (as expounded in [7], for example) may be applied to the rationalisation F Q to yield an isomorphism…”
Section: The Rational Relationsmentioning
confidence: 99%
“…The analytic and function theoretic viewpoint has prospered in Russian literature, whereas the homotopical approach has featured mainly in the west; the machinery of formal group laws, however, has been well-oiled by both schools, and the rôle of index theory has been enhanced by many authors since it was originally suggested by Gelfand [40]. Ironically, the dichotomy between the first and second is illustrated by comparing computations of the Chern-Dold character [15] with applications of the Boardman homomorphism and Hurewicz genus [79]. In essence, these bear witness to the remarkable influence of Novikov and Adams respectively.…”
Section: Introductionmentioning
confidence: 99%